Effects of Varying Lipid Sources as Alternatives to Zinc Oxide or Carbadox on Nursery Pig Growth Performance and Fecal Consistency - P. L. Dahmer; G. E. Luebcke; A. B. Lerner; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 360 weaned pigs (DNA; 241 × 600; initially 11.9 ± 0.02 lb) were used in a 35-d study evaluating the ability of varying lipid sources to replace ZnO or carbadox in early nursery pig diets. Pigs were weaned at approximately 21 days of age and allotted to pens based on initial weight in a completely randomized design to one of six dietary treatments: 1) Negative control (no added ZnO or carbadox); 2) Control + 3,000 ppm Zn from ZnO in phase 1 and 2,000 ppm Zn in phase 2; 3) Control + 50 g/ton carbadox; 4) Control + 1% C6:C8:C10 medium chain fatty acid (MCFA) blend; 5) Control + 1% Proprietary Oil Blend (Feed Energy Corp., Des Moines, IA); and 6) Control + 1% monolaurate blend (FORMI GML from ADDCON, Bitterfeld- Wolfen, Germany). There were 6 pigs assigned to each of the 10 replicate pens per treatment. All experimental diets were isocaloric, with choice white grease used to balance the energy level. From d 0 to 19, pigs fed the ZnO or carbadox diets had greater (P<0.05) average daily gain (ADG) than pigs fed the control or Feed Energy oil blend, with pigs fed the MCFA blend or FORMI GML intermediate. These effects were mostly driven by feed intake, which was greater (P<0.05) in pigs fed diets containing ZnO or carbadox than by pigs fed diets containing the 1% MCFA or Feed Energy oil blends. Dietary treatment had a marginally significant effect (P>0.078) on feed efficiency (F/G), with the best feed efficiency for pigs fed carbadox and the poorest feed efficiency in pigs fed the control diet. Both ZnO and carbadox improved (P<0.05) fecal consistency during the treatment period. In summary, ZnO and carbadox continue to be valuable additives to maximize growth in early nursery pig diets. Some lipid products, such as the monolaurate-containing FORMI GML, show greater promise to replace these antimicrobials than others. These findings suggest that additional research is warranted to identify optimal lipid blends that can replace feed-based antimicrobials in early nursery pig diets without negatively impacting fecal consistency or feed intake.
Keywords: lipid sources; nursery pig; antibiotic alternatives; carbadox